PENDIDIKAN, MASA JABATAN DIREKTUR UTAMA DAN PENGUNGKAPAN CORPORATE SOSIAL RESPONSIBILITY (CSR) - Azmida L Kwalomine (Jurnal Riset Akuntansi Terpadu, 2018)
This study exmined the education and tenure of Presiden Director and consistency in Corporate Social Responsibility (CSR) action, wich in State Owned Enterprises known as Partnership and Comunity Development Program. The purpose of this study was to examine the education and tenure of President Director on the quality of Partnership and Comunity Development Program.  The sample of this study are state owned enterprises with the total population are 119 firms, based on the sampling criteria, the final sample of this study are 50 firms. Content analysis method was used to measure the quality of Partnership and Comunity Development Program. Data was analysed by SPSS program. Multiple linear regression model was used to test the hypothesis. The result shows that education and tenure have insignificant effect toward the quality of Partnership and Comunity Development Program. Future research could investigate other variables that could affect the quality of Partnership and Comunity Development Program.